Multi-Agent Resilient Control Based on False Data Injection Attacks - Yu, Wenduo; Guo, Zongjin; Suo, Pengxiang; Li, Nan; Song, Ziyi; Deng, Linjiang (2024 Second International Conference on Cyber-Energy Systems and Intelligent Energy (ICCSIE), 2024)
The paper introduces a resilient control method for nonlinear multi-agent systems (MAS). The attack type considered in this paper is FDI (False Data Injection) attacks targeting the controller. The consequence of the attack is the occurrence of controller malfunction. In industrial control systems, FDI attacks pose a significant security threat. Instead of relying on global information about the communication network, this method allows agents to exchange information locally with their neighboring agents. Each agent has its own control mechanism, which helps avoid the need for centralized communication. Furthermore, this approach addresses the issue of elastic control in the presence of FDI attacks. It ensures that the system can continue to operate smoothly even when encountering unknown abnormal parameters. By carefully selecting Lyapunov functions, the paper demonstrates that the system achieves stable consensus between leaders and followers in a multi-agent setting.